ANALYSIS OF CRITICAL THINKING SKILLS BY HOMESCHOOLING’S STUDENTS IN SOLVING MATHEMATICAL PROBLEM - Sholihah, Fitriatus; Inganah, Siti; Effendi, Moh. Mahfud (Study Program of Mathematics Education University of Muhammadiyah Malang, 2017)
This study aims to describe the critical thinking skills ofhomeschooling students in solving mathematical problems. The type ofthis research is descriptive research with qualitative approach. Subjects inthis study were six students homeschooling is equivalent to junior highschool students class IX. Data were obtained through tests and interviews.Test are identified and described in accordance with the achievement ofstudents towards critical thinking indicators used in this research thatclarification, assessment, strategy/ tactics, and inference. The results of theinterviews are used to further strengthen the data on homeschoolingstudents' critical thinking skills. The results showed that onehomeschooling student is in the category of less critical, four students areon quite critical category and only one student in a critical category.This suggests that homeschooling students' critical thinking skills arelow. Low critical thinking skills are affected by limitations homeschoolingstudent learning of mathematics is done, students 'mathematical ability andmathematical learning processes that do not yet geared to developinghomeschooling students' critical thinking skills. So that based on the resultsof this study are advised to make the learning process of mathematics todevelop homeschooling students' critical thinking skills.